Immediate and Durable Clinical Improvement in the Non-Operated Hand after Contralateral Surgery for Patients with Bilateral Carpal Tunnel Syndrome. (September 2015) - Unno, F.; Lucchina, S.; Bosson, D.; Fusetti, C.
Background: Little is known about clinical improvement in the non-operated hand after unilateral surgery for patients who present with bilateral carpal tunnel syndrome (CTS). In this prospective study of patients with bilateral CTS, we evaluated the clinical effects on the non-operated hand following unilateral contralateral carpal tunnel surgical release. Material and Methods During a consecutive period of 22 months, 69 patients with bilateral CTS underwent unilateral open carpal tunnel release. Bilateral subjective and objective evaluations were performed pre-operatively, at days 2, 15 and 180 after surgery. Subjective evaluations, analysed with Student t test, included the Boston-Levine symptom severity score and a visual analogue scale including pain, nocturnal symptoms and numbness. A telephone survey was conducted 12 months after surgery. Results: The Boston-Levine severity score of the contralateral non-operated hand decreased from 2.70 pre-operatively to 1.70 at 2 days ( p <0.001). The visual analogue pain score decreased at 2 days for 61 patients (88 %), whereas the nocturnal symptoms decreased or disappeared in 63 cases (91 %) and the paresthesia in 52 cases (75 %) ( p s<0.001). These beneficial effects were stable in time with no statistically significant change at 180 days. Overall, 58 patients (84 %) observed a total resolution or a significant improvement in their symptoms at 6 months. At 12 months, 100 % of patients responded to a telephone survey. Fifty one of them (74 %) reported minimal or no symptoms on the non-operated hand. Linear regression (analysis of variance [ANOVA]) showed that gender, age, professional status, duration of preoperative symptoms and severity of electrophysiological disturbances were not predictive of post-operative evolution in the non-operated hand after unilateral surgery for CTS.